Production of lactic acid and fructose from media with cane sugar using mutant of Lactobacillus delbrueckii NCIM 2365 - Patil, S. S.; Kadam, S. R.; Patil, S. S.; Bastawade, Kulbhushan B.; Khire, Jayant Malhar; Gokhale, D. V. (Letters in Applied Microbiology, 2006)
Aims: To examine the potential of Lactobacillus delbrueckii mutant, Uc-3 to produce lactic acid and fructose from sucrose-based media. Methods and Results: The mutant of L. delbrueckii NCIM 2365 was cultivated in shake flask containing hydrolysed cane sugar (sucrose)-based medium. The lactic acid yield and volumetric productivity with hydrolysed cane concentration up to 200 g l(-1) were in the range of 92-97% of the theoretical value and between 2.7 and 3.8 g l(-1) h(-1), respectively. The fructose fraction of the syrup produced was more than 95% when the total initial sugar concentration in the medium was higher (150-200 g l(-1)). There are no unwanted byproducts detected in the fermentation broth. Conclusions: We demonstrated that L. delbrueckii mutant Uc-3 was able to utilize glucose preferentially to produce lactic acid and fructose from hydrolysed cane sugar in batch fermentation process. Significance and Impact of the Study: These findings will be useful in the production of lactic acid and high fructose syrups using media with high concentrations of sucrose-based raw materials. This approach can lead to modification of the traditional fermentation processes to obtain value-added byproducts, attaining better process economics.
Keywords: fructose accumulation; hydrolyzed cane sugar; lactic acid production; Lactobacillus delbrueckii; Mutant

Protoplast formation and regeneration in lactobacillus delbrueckii - Singhvi, Mamta; Joshi, Dipti; Gaikaiwari, Shalaka A.; Gokhale, Digambar V. (Indian Journal of Microbiology, 2010)
Method for production and regeneration of Lactobacillus delbrueckii protoplasts are described. The protoplasts were obtained by treatment with a mixture of lysozyme and mutanolysin in protoplast buffer at pH 6.5 with different osmotic stabilizers. The protoplasts were regenerated on deMan, Rogosa and Sharpe (MRS) with various osmotic stabilizers. Maximum protoplast formation was obtained in protoplast buffer with sucrose as an osmotic stabilizer using a combination of lysozyme (1 mg/ml) and mutanolysin (10 mu g/ml). Maximum protoplast regeneration was obtained on MRS medium with sucrose (0.5 M) as an osmotic stabilizer. The regeneration medium was also applicable to other species of lactobacilli as well. This is, to our knowledge, the first report on protoplast formation and efficient regeneration in case of L. delbrueckii.
Keywords: Lactobacillus delbrueckii; Protoplast formation; Protoplast regeneration